Developing writers in higher education : a longitudinal study - Gere, Anne Ruggles, 1944- (Digital rhetoric collaborative., 2019)
"There have been several studies of college student writers' development across the undergraduate years, but this book is the largest and most comprehensive because it includes extensive data on 169 students, and each chapter raises different questions and offers a new perspective on writerly development. At a time when the value of a college education is being questioned, this book offers clear evidence of how undergraduates move toward becoming effective writers. While there is no shortage of complaints about writing skills in the general population, there is relatively little appreciation for and understanding of the kinds of investments, of both funds and commitment, necessary to address this need. Students do not all follow the same path, of course, but this book shows how writing for various purposes in multiple disciplines leads them to new levels of competence"--